Propuesta para análisis y estandarización de procesos: Planta de Procesamiento de la Corporación Hortícola Nacional - Blanco-Chaves, José Ignacio (2025)
A methodology based on best practices in process analysis is proposed, aimed at reducing rework and standardizing the activities carried out at the processing plant of the National Horticultural Corporation. Its application to the process “Managing Orders for Agricultural Products” has proven to be feasible, achieving a significant reduction in rework and errors, and increasing operational efficiency by 29% compared to the previous cycle time. Moreover, the percentage of non-value-added activities decreased from 60% to 39%, while tasks that add value to the customer and the business increased by 16%. The implementation of this methodology is projected to yield direct benefits in process standardization, knowledge management, enterprise resource planning, and the reduction of rework, among other areas.